A Framework for Simulation, Optimization and Information Management of Physically-Coupled Systems of Systems. Issue 3 (2015) - Kampert, David; Nazari, Shaghayegh; Sonntag, Christian; Epple, Ulrich; Engell, Sebastian
Abstract: The paper deals with the optimization of the operation of so-called systems of systems, i.e. large systems where the subsystems possess some autonomy but the system as a whole has to be operated optimally. Specifically, the focus is on systems of systems that are physically coupled, e.g. electric grids or production plants that are coupled by flows of matter and energy. Besides the development of suitable distributed optimization methods for reducing operational costs, the method's validation, integration and log-term use in real installations is a major challenge. To ensure maintainability and adaptability of the optimized management, the information exchange between the system and the optimization methods has to be addressed. A concept for an information exchange platform was developed as part of the European project DYMASOS. Requirements for the platform and validation scenarios are derived from industrial case studies.